The effects of gene polymorphisms on glioma prognosis. (8th November 2017) - Cui, Ying; Li, Guolin; Yan, Mengdan; Li, Jing; Jin, Tianbo; Li, Shanqu; Mu, Shijie
Abstract: Background: Malignant gliomas are the most common primary brain tumors. Various genetic factors play important roles in the development and prognosis of glioma. The present study focuses on the impact of MPHOSPH6, TNIP1 and several other genes ( ACYP2, NAF1, TERC, TERT, OBFC1, ZNF208 and RTEL1 ) on telomere length and how this affects the prognosis of glioma. Methods: Forty‐three polymorphisms in nine genes from 605 glioma patients were selected. The association between genotype and survival outcome was analyzed using the Kaplan–Meier method, Cox regression analysis and the log‐rank test. Results: The 1‐year overall survival (OS) rates of patients younger than 40 years of age was higher compared to those in patients older than 40 years of age. The 1‐year OS rate of patients who underwent total resection was higher than that of patients whose gliomas were not completely resected. The 1‐year OS rates of patients undergoing chemotherapy and of patients who did not undergo chemotherapy were 39.90% and 26.80%, respectively. Univariate analyses showed that ACYP2 rs12615793 and TERT rs2853676 loci affected progression‐free survival in glioma patients; both ZNF208 rs8105767 and ACYP2 rs843720 affected the OS of patients with low‐grade gliomas. Multivariate analyses suggested that MPHOSPH6 rs1056629 and rs1056654, and TERT rs2853676 loci were associated with good prognoses of patients with glioma or high‐grade gliomas, whereas ZNF208 rs8105767 was associated with good prognosis of patients with low‐grade glioma. Conclusions: Age, surgical resection and chemotherapy influenced the survival rates of glioma patients. TERT, MPHOSPH6, ACYP2 and ZNF208 genes were found to affect glioma prognosis.